Residential retrofit : 20 case studies - Baeli, Marion (London : RIBA Publishing, 2013)
'The essence of sustainability in buildings is their capability to adapt to change over time. The UK has a large housing stock that has been developed and evolved over generations, and become the fabric and character of our cities, towns and neighbourhoods. The capability of buildings to adapt to changing lifestyles is the root of their sustainability. When buildings do not adapt they are disposed of, since it is only active use that confers value. It is only value that provides necessary investment for renewal. Residential Retrofit presents a series of innovative and best practice case studies of residential low energy retrofit projects, and illustrates what has been achieved in practice in the UK.'--Publisher's website.
Keywords: Buildings -- Repair and reconstruction -- Case studies; Dwellings -- Remodeling -- Case studies; Sustainable buildings -- Case studies; Buildings -- Energy conservation -- Case studies